Changes of repolarization parameters after left bundle branch area pacing and the association with echocardiographic response in heart failure patients - Li, Yao; Lu, Wenzhao; Hu, Qingyun; Cheng, Chendi; Lin, Jinxuan; Zhou, Yu’an; Chen, Ruohan; Dai, Yan; Chen, Keping; Zhang, Shu (Frontiers in Physiology, 2022)
Background: Left bundle branch area pacing (LBBAP) has become a safe and effective option for heart failure (HF) patients indicated for cardiac resynchronization therapy (CRT) and/or ventricular pacing, yet the response rate was only 70%. Repolarization parameters were demonstrated to be associated with cardiac mechanics and systolic function. This study aimed to investigate the effects of LBBAP on repolarization parameters and the potential association between those parameters and echocardiographic response. Methods and results: A total of 59 HF patients undergoing successful LBBAP were consecutively included. QTc, Tpeak-Tend (TpTe) and TpTe/QTc were measured before and after the implantation. The results turned out that the dispersion of ventricular repolarization (DVR) improved after LBBAP among the total population. Although trends of repolarization parameters varied according to different QRS configurations at baseline, the post-implant parameters showed no significant difference between groups. The association between repolarization parameters and LBBAP response was then evaluated among patients with wide QRS. Multivariate analysis demonstrated that post-implant TpTe was the independent predictor of LBBAP response (P<0.05). Receiver operating characteristic analysis indicated an area under curve of 0.77 (95% CI, 0.60-0.93) with a cutoff value of 81.2ms (P <0.01). Patients with post-implant TpTe<81.2ms had a significantly higher rate of echocardiographic response (93.3 vs 44.4%, P<0.01). Further subgroup analysis indicated that the predictive value of post-implant TpTe for LBBAP response was more significant in non-left bundle branch block (LBBB) patients than LBBB patients. Conclusions: LBBAP improved DVR significantly in HF patients. Post-implant TpTe was associated with echocardiographic response after LBBAP among patients with wide QRS, especially for non-LBBB patients.